Characteristic pulse detection method for fuzzy area - Xin Geng; Baoqiang Du (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2022)
In order to achieve higher frequency measurement accuracy, this paper proposed a characteristic pulse detection method of fuzzy area based on the quantized phase processing method of different frequency groups. First, the fuzzy area of the group phase coincidence points continuously moved on the time axis after passing through delay elements. The moving distance, that is, the number of the delay elements was determined by the main clock cycle of the D flip-flop. After that, three groups of phase coincidence detection fuzzy areas in different positions were sent to the digital logic module to extract the edge pulses of the phase coincidence detection fuzzy area. The pulse width is determined by the difference between the clock cycles of the delay elements. The clock cycles of different delay units were adjusted to obtain nanosecond or even picosecond circuit detection resolution. Finally, the pulses generated at the edge of the phase coincidence fuzzy area are taken as the switching signal of the frequency signal counter, so the stability of the gate signal and the accuracy of the gate time measurement are improved. The experimental results show that frequency stability can reach the order of E-13/s. In addition, compared with the traditional measurement method, it is characterized by simple structure, low cost, low noises, and high measurement resolution.